2011
DOI: 10.1615/intjmedmushr.v13.i2.110
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Submerged Cultivation Conditions on Mycelial Biomass and Protease Production by Lentinus citrinus Walleyn et Rammeloo DPUA 1535 (Agaricomycetideae)

Abstract: The influence of different carbon and nitrogen sources, pH of the culture medium, and temperature and period of cultivation on mycelial biomass production and protease activity by Lentinus citrinus DPUA 1535 were investigated in submerged culture. A 2(5) full factorial design with three central points was employed, and the results showed that at a significance level of 95% only nitrogen source and temperature were statistically significant for mycelial biomass production. On the other hand, for protease activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…All stock cultures were maintained on a potato dextrose agar (PDA) supplemented with 0.5% (w/v) yeast extract (YE) (HiMedia, Mumbai, India) slant, subcultured and incubated at 25 °C for eight days in the dark and then stored at 4 °C. 13 …”
Section: Methodsmentioning
confidence: 99%
“…All stock cultures were maintained on a potato dextrose agar (PDA) supplemented with 0.5% (w/v) yeast extract (YE) (HiMedia, Mumbai, India) slant, subcultured and incubated at 25 °C for eight days in the dark and then stored at 4 °C. 13 …”
Section: Methodsmentioning
confidence: 99%
“…The values obtained for the edible mushroom L. citrinus was also superior to that obtained by Kirsch et al (2011) who studied the mushroom of the same species. And still, values higher than that of protease activity (50.03 U/mL) was obtained by Khaund and Joshi (2014) that investigated the enzymatic profiling of wild edible mushrooms consumed by the ethnic tribes of India.…”
Section: Determination Of Proteolytic Activitymentioning
confidence: 39%
“…High cell density, is also required for efficient protease biosynthesis. 43 , 44 The determination coefficient for the model was 0.9852, which indicated that the model fit well with the data. The lack of fit was 0.1769, which was not significant relative to the pure error.…”
Section: Discussionmentioning
confidence: 80%